The new Shudras’s rebellion - Aróstica Maldonado, Iván (Derecho Público Iberoamericano, 2022)
On top of a class struggle in the material field of “having”, the stake is currently taking place led by an unprecedented conglomerate of revolutionary subjects, replacements of the proletariat, tending to impose on the entire community a new way of “being”, nullifying the imaginary collective based on the Greco-Christian worldview that still, bloodless, beats in society. In line with a certain ideology that moves towards a new format of the eternal anarchist dream: “Neither God, nor Country, nor King”, and with the help of a sub-discourse that has allowed them to obtain hegemony in the cultural sphere, they seek to irrevocably consolidate it through through a new Constitution that sponsors and promotes its “legal revolution”.